Moral emotions and altruistic behavior (2007)
According to evolution's theory, the unconditional altruist behavior (the behavior that it gives indistinctly to parents and no parents) is biological and psychologically impossible. For this theory, it is not possible that one individual increases the aptitude of the others and the same time lows his aptitude without expectations. Against to the skeptical evolutionist, recent advances shown the possibility of the altruist behavior, and suggest that it has to do with the moral emotions. In this paper I refer some of these advances that suggest that some kind emotions can contribute to individual's interest as well as group's interest.